(untitled) (Historia, 2021)
The centenary commemoration of the First World War (1914 – 1918), also once known as The Great War, has stirred worldwide interest in the events, leading to a number of important publications seeing the light in recent years. From a South African perspective, the First World War (WWI) had an important impact on the Union of South Africa and sparked civil unrest in the form of a rebellion in protest to South African involvement in WW1. The story of South Africa’s involvement in South West Africa is rather well known and is considered by many as the first allied victory of WWI. The events surrounding the sinking of the SS Mendi is however more obscure and it is also now accepted that the tragedy of the sinking of the SS Mendi forms a neglected part of South African historiography due to the fact the role of the labourers in WWI has not been fully acknowledged in the past. This is of course not unique to South African historiography, as noted by Gribble and Scott. Despite the important role that the labourers played in the war, their role has not been acknowledged in history books (p. 15).